The comparative burden of brain and central nervous system cancers from 1990 to 2021 between China, the United States, the United Kingdom, and Japan - Zirui Li; Xin Chen; Shuai Han; Anhua Wu (BMC Public Health)
Abstract Background Brain and central nervous system (CNS) cancers impose a substantial and growing disease burden in China, marked by elevated mortality and disability rates. Understanding disparities in cancer control strategies between China and developed countries (the US, the UK, and Japan) may inform evidence-based policy improvements. Methods Using Global Burden of Disease (GBD) 2021 data, we analyzed incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for brain and CNS cancers (1990–2021). Trends were assessed via estimated annual percentage change (EAPC), while frontier analysis evaluated disease burden reduction capacity relative to socioeconomic development. Health inequalities were measured using the Slope Inequality Index (SII) and Concentration Index. Future trends were projected via ARIMA models. Results In 2021, China reported 105,541 new cases and 68,911 deaths. While China had lower age-standardized incidence (ASIR) and prevalence (ASPR) rates than comparison nations, its DALYs rate was higher. From 1990 to 2021, ASIR and ASPR increased universally, whereas age-standardized mortality (ASMR) and DALYs (ASDR) declined in China, the US, and the UK but rose in Japan. High-SDI regions exhibited greater burden mitigation capacity, with widening cross-country inequalities. Projections indicate rising ASIR in all nations by 2036. Conclusions Despite declining mortality, China’s brain and CNS cancer burden remains disproportionately high. Policymakers should integrate effective strategies from developed nations while tailoring interventions to China’s unique epidemiological and healthcare context.